Intimate Betrayal : Domestic Violence in Lesbian Relationships. - Kaschak, Ellyn (Taylor and Francis, 2014)
Help ease the secret suffering of lesbians in abusive relationships!Why is woman-on-woman violence so often ignored or discounted? Intimate Betrayal: Domestic Violence in Lesbian Relationships uncovers the hidden problem of lesbians who hurt the women they love. This long-needed book brings together theory, practice, and research to suggest new and fruitful ways to understand, prevent, and treat this common problem. Intimate Betrayal provides new empirical research into the psychological and sociocultural causes of abuse. As several of the chapter authors demonstrate, neith.